34 Do Centres that Usually Perform Percutaneous Coronary Intervention Trans-Radially have Inferior Outcomes when Operating Trans-Femorally?. (3rd June 2016) - Hulme, William; Sperrin, Matthew; Kontopantelis, Evan; Ludman, Peter; Belder, Mark de; Nolan, James; Mamas, Mamas A
Abstract : Background: Over the last decade trans-radial access (TRA) has become more common than trans-femoral access (TFA) for Percutaneous Coronary Intervention (PCI) in the UK. Despite studies highlighting the benefits of this transition, there are concerns that the resulting drop in TFA activity has led to operators and centres losing TFA proficiency, compromising the safety and efficacy of procedures where TFA is necessary. Aims: To evaluate the impact of each centre's recent experience of the TFA approach on procedural outcomes in TFA-only procedures. Methods: This retrospective cohort study used procedures recorded in the British Cardiovascular Intervention Society (BCIS) PCI audit from 2007 to 2013 in England and Wales. Centres were split into one of three groups depending on the proportion of total procedures undertaken via TFA in 2013, with patient and procedural characteristics for TFA-only procedures observed within these groups over time. By considering each centre's access site choices in the 12 months prior to procedure date, simply-derived measures were used to capture the 'recent TFA experience' of the operating centre for each procedure. The association of these measures on 30-day mortality, after risk-adjustment, were then studied using multiple logistic regression. Results: A total of 235, 474 procedures were available for analysis. Unadjusted TFA-only mortality in centres who were early-adopters of TRA increased more rapidly than for centres who maintained high TFA activity, and this was driven by higher baseline risk. After case-mix adjustment, recent TFA experience was found to have no effect on 30-day mortality (OR=0.99 per 0.1 increase in recent TFA proportion; CI=0.96 to 1.01; p = 0.220), with similar results when restricting to procedures with low clinical-complexity (OR=0.98 per 0.1 increase in recent femoral proportion; CI=0.95 to 1.01; p = 0.245). Conclusions: Poorer TFA outcomes for predominantly high TRA centres are driven by the propensity of these centres to utilise TFA in the highest risk patients. Once differences in case mix are adjusted for, TFA outcomes are similar between high and low radial proportion centres, with no evidence to suggest that increasing unfamiliarity with the TFA technique is detrimental. The outcome gains achieved by the national adoption of TRA is not attenuated by a loss of TFA proficiency, and centres should be encouraged to continue to adopt TRA as the default access site for PCI wherever possible.